Development of a biomimetic bioreactor for regenerative endodontics research. (25th August 2022) - Louvrier, Aurélien; Kroemer, Marie; Terranova, Lisa; Meyer, Florent; Tissot, Marion; Euvrard, Edouard; Gindraux, Florelle; Meyer, Christophe; Rolin, Gwenaël
Abstract: In the context of regenerative endodontics research with the development of biomaterials, this work aimed to develop and test a prototype biomimetic bioreactor of a human tooth. The bioreactor was designed to reproduce a shaped dental canal connected with a cavity reproducing the periapical region and irrigated through two fluidic channels intended to reproduce the apical residual vascular supply. A test biomaterial composed of polylactic acid/polycaprolactone‐tannic acid (PLA/PCL‐TA) was produced by electrospinning/electrospraying and calibrated to be inserted in a dental canal. This biomaterial was first used to evaluate its imbibition capacity and the oximetry inside the bioreactor. Then, Dental Pulp Stem Cells (DPSCs) were cultured on PLA/PCL‐TA cones for 1–3 weeks in the bioreactor; afterward cell adhesion, proliferation, and migration were histologically assessed. Complete imbibition biomaterial was obtained in 10 min and oximetry was stable over time. In the bioreactor, DPSCs were able to adhere, proliferate and migrate onto the surface and inside the biomaterial. In conclusion, this bioreactor was used successfully to test a biomaterial intended to support pulp regeneration and constitutes a new in vitro experimental model closer to clinical reality.